2018
DOI: 10.1590/1678-4324-2018161223
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Low-level Laser Therapy on Muscle Repair in Rats with Chronic Alcohol Intake

Abstract: This study aimed to investigate the effects of low-level laser therapy (LLLT) on muscle repair in rats with chronic alcohol intake. Thirty male Wistar rats were distributed into three groups: injured tibialis anterior (TA) muscle without treatment (IC); chronic ingestion of alcohol plus injured TA muscle (AI); and chronic ingestion of alcohol plus injured TA plus LLLT (AIL). Each group was divided into two different subgroups, and rats were sacrificed on days 3 and 7 post-injury. Morphological features in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 28 publications
0
2
0
Order By: Relevance
“… 103 In a model of cryoinjury of tibialis anterior muscle, chronic alcohol administration increased inflammation, and low-level laser therapy decreased inflammation and improved recovery. 142 In a model of SKM disuse, chronic alcohol feeding for 10 weeks in ovariectomized or intact female rats indicated that alcohol dysregulated genes implicated in regeneration and increased TGF-beta expression. 134 In addition, primary macaque myoblasts isolated from in vivo CBA-administered macaques had decreased differentiation potential and concomitant decrease in myogenic gene expression, 76 indicating that alcohol could affect SKM regenerative potential.…”
Section: Results Of the Reviewed Studiesmentioning
confidence: 99%
“… 103 In a model of cryoinjury of tibialis anterior muscle, chronic alcohol administration increased inflammation, and low-level laser therapy decreased inflammation and improved recovery. 142 In a model of SKM disuse, chronic alcohol feeding for 10 weeks in ovariectomized or intact female rats indicated that alcohol dysregulated genes implicated in regeneration and increased TGF-beta expression. 134 In addition, primary macaque myoblasts isolated from in vivo CBA-administered macaques had decreased differentiation potential and concomitant decrease in myogenic gene expression, 76 indicating that alcohol could affect SKM regenerative potential.…”
Section: Results Of the Reviewed Studiesmentioning
confidence: 99%
“…Regardless of the diet and the biomaterial used, some complementary therapies have the ability to favor and increase the volume of new bone formed, reducing postoperative recovery time, reducing edema and pain, such as photobiomodulation with the use of low-level laser [45][46][47][48][49]. Photobiomodulation was also able to increase the expression of myogenic and vascular growth factors and stimulate skeletal muscle regeneration in rats with chronic alcohol intake [50].…”
Section: Histomorphometric and Statistical Analysismentioning
confidence: 99%